Reconstructing biogeographic temporal events in the evolution of the livebearer fish genus Jenynsia based on total evidence analysis (Cyprinodontiformes: Anablepidae). Issue 2 (17th February 2019) - Amorim, Pedro F.; Costa, Wilson J. E. M.
Abstract : The current distribution of the Neotropical ichthyofauna has been widely affected by the main geological events that occurred in South and Central America. However, robust biogeographic information is still scarce or absent for most fish families. The biogeographic relationships of the most diverse anablepid genus, Jenynsia, are herein analysed, using temporal and spatial approaches based on a total evidence dataset, including 167 morphological characters and seven nuclear genes, totalling 6075 bp. A time calibrated analysis recovered the origin of Jenynsia at the Miocene and the diversification of its two subgenera between the Late Miocene and Early Pliocene. This result combined with the analysis of reconstruction of ancestral states indicates that the ancestor of Jenynsia colonized the Paranean Sea, and the current distribution of the species of the genus is probably a result of geological events, including: (1) ancient connections between Iguaçu and upper Uruguay River basins; (2) sea level variation along the Pliocene in the South American Atlantic coast; and (3) the decrease of the Paranean Sea along the Pliocene and Pleistocene.